1957
DOI: 10.1104/pp.32.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tobacco Alkaloids. II. The Formation of Nicotine and Nornicotine in Tobacco Supplied with N15.

Abstract: The preceding paper (11) Craig counterculrrent apparatus (2) was used. In the course of this development the separation of a mixture prepared from nicotine, nornicotine, and anabasine was investigated by means of this apparatus,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

1958
1958
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…This conclusion is based on nornicotine levels rising "at the expense of" nicotine levels in both green and cured leaf (3,4,21,23), and isotopic labeling studies (10,19). Other studies have indicated that nornicotine may be synthesized independently of nicotine (8,9,22). Putrescine was oxidized 40o as well as N-methylputrescine (15), and the enzymic oxidation product of putrescine is 4-aminobutanal, which after spontaneous cyclization to pyrroline might be utilized to synthesize nornicotine.…”
mentioning
confidence: 99%
“…This conclusion is based on nornicotine levels rising "at the expense of" nicotine levels in both green and cured leaf (3,4,21,23), and isotopic labeling studies (10,19). Other studies have indicated that nornicotine may be synthesized independently of nicotine (8,9,22). Putrescine was oxidized 40o as well as N-methylputrescine (15), and the enzymic oxidation product of putrescine is 4-aminobutanal, which after spontaneous cyclization to pyrroline might be utilized to synthesize nornicotine.…”
mentioning
confidence: 99%
“…The Knowledge has accumulated as to the role of pectinase in plant disease (1,12,13,14). In this paper evidence will be presented that pectinase preparations can cause a respiratory acceleration and increase of the activities of polyphenol oxidase and peroxidase in host tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The conversion of nicotine to norniicotine occurred only at a later stage of plant development (2,13 All the grafted plants with N. glaufca scion had no nicotine regardless of whether the grafted stock was nicotine type or nornicotine type. Three possible explanations are suggested as follows: A) The formation of anabasine in the N. glauica scion is at the expense of nicotine, although it had been demonstrated that anabasine was not formeed by rearrangement of the nicotine molecule (14); B) there is an active demethylation system in N. glauca scion in which nicotine was converted to nornicotine; and C) the pathway of nicotine formation was intercepted at the stage of nornicotine because of the absence of the specified methylation system in N. glauca scion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations